Anti-Inflammatory and Healing Activity of the Hydroalcoholic Fruit Extract of Solanum diploconos (Mart.) Bohs - Larissa Benvenutti; Roberta Nunes; Ivonilce Venturi; Silvia Aparecida Ramos; Milena Fronza Broering; Fernanda Capitanio Goldoni; Sarah Eskelsen Pavan; Maria Verônica Dávila Pastor; Angela Malheiros; Nara Lins Meira Quintão; Elizabeth Soares Fernandes; José Roberto Santin (Journal of Immunology Research)
Background. Solanum diploconos (Mart.) Bohs is a native Brazilian plant belonging to the Solanaceae family, popularly known as “tomatinho do mato” and poorly investigated. Herein, we presented for the first time evidence for the anti-inflammatory and wound healing activities of S. diploconos fruit hydroalcoholic extract. Material and Methods. In vitro fMLP-induced chemotaxis, LPS-induced inflammatory mediator levels (cytokines by ELISA and NO release by Griess reaction), and adhesion molecule expression (CD62L, CD49d, and CD18, by flow-cytometry) were assessed in neutrophils treated with different concentrations of the extract. Inflammation resolution was measured by the efferocytosis assay and the healing activity by in vivo and in vitro assays. The air pouch model of carrageenan-induced inflammation in Swiss mice was used to investigate the in vivo anti-inflammatory effects of the extract. Leukocyte influx (by optical microscopy) and cytokine release were quantified in the pouch exudates. Additionally, the acute and subacute toxic and genotoxic effects of the extract were evaluated. Results. In vitro, the extract impaired neutrophil chemotaxis and its ability to produce and/or release cytokines (TNFα, IL-1β, and IL-6) and NO upon LPS stimuli (p<0.01). LPS-treated neutrophils incubated with the extract presented increased CD62L expression (p<0.01), indicating a reduced activation. An enhanced efferocytosis of apoptotic neutrophils by macrophages was observed and accompanied by higher IL-10 and decreased TNFα secretion (p<0.01). In vivo, similar results were noted, including reduction of neutrophil migration, protein exudation, and cytokine release (p<0.01). Also, the extract increased fibroblast proliferation and promoted skin wound healing (p<0.01). No signs of toxicity or genotoxicity were observed for the extract. Conclusion. S. diploconos fruit extract is anti-inflammatory by modulating neutrophil migration/activation as well macrophage-dependent efferocytosis and inflammatory mediator release. It also indicates its potential use as a healing agent. Finally, the absence of acute toxic and genotoxic effects reinforces its possible use as medicinal product.